Two-carbon tethered artemisinin–isatin hybrids: design, synthesis, anti-breast cancer potential, and in silico study - Wang, Ruo; Huang, Renhong; Yuan, Yaofeng; Wang, Zheng; Shen, Kunwei (Frontiers in Molecular Biosciences, 2023)
Eleven two-carbon tethered artemisinin-isatin hybrids (4a-k) were designed, synthesized, and evaluated for their antiproliferative activity against MCF-7, MDA-MB-231 and MDA-MB-231/ADR breast cancer cell lines as well as cytotoxicity towards MCF-10A cells in this paper. Among them, the representative hybrid 4a (IC50: 2.49-12.6 µM) was superior to artemisinin (IC50: 72.4->100 µM), dihydroartemisinin (IC50: 69.6-89.8 µM) and adriamycin (IC50: 4.46->100 µM) against the three tested breast cancer cell lines. The structure-activity relationship revealed that the length of the alkyl linker between artemisinin and isatin was critical for the activity, so further structural modification could focus on evaluation of the linker. The in silico studies were used to investigate the mechanism of the most promising hybrid 4a. Target prediction, bioinformatics, molecular docking, and molecular dynamics revealed that the most promising hybrid 4a may exert anti-breast cancer activity by acting on multiple targets such as EGFR, PIK3CA, and MAPK8 and thus participating in multiple tumor-2 related signaling pathways.